DAKWAH COMMUNITY ECONOMIC DEVELOPMENT - fitria, dona (Spektra: Jurnal Ilmu-ilmu Sosial, 2020)
Da'wah for the development of society and the people is an activity of the Prophet sallallaahu Wassalam which is supported by an established economy. This we can see how the gait of the Prophet sallallaahu Wassalam with Ummul the believer Khadijah radhiallahu'anhu in preaching to improve the condition of the people from the downturn of civilization. Likewise, the companions of the Prophet Muhammad, carried out the mission of da'wah at the expense of their wealth. How did Uthman bin Affan sacrifice buying a well from a Jew for the Muslims. What about his wealth Abu Bakr freed the slaves. There are many examples in Islam about the sacrifice of wealth in preaching. In addition to government policies, community economic empowerment can be carried out, including by opening a business unit. With the existence of a business unit, it will create jobs that absorb human labor. The businesses developed vary from simple business units in the form of MSMEs, home industries, cooperatives, as well as large managed business units such as factories, tourism offices, banking and so on. It is time for Muslims to unite in advancing the economy so that Muslims are free from the shackles and colonialism in the capitalist, hedonistic and materialistic era by moving the people's economy, in the form of establishing sharia markets, sharia-based tourism activities, as well as the government's attitude that issues pro-independence economic policies. Islamic law and support Islamic banking programs in Indonesia.